2000
DOI: 10.1038/sj.leu.2401843
|View full text |Cite
|
Sign up to set email alerts
|

Double induction strategy including high dose cytarabine in combination with all-trans retinoic acid: effects in patients with newly diagnosed acute promyelocytic leukemia

Abstract: A prospective multicenter study was performed to investigate the clinical and molecular results of intensified double induction therapy including high-dose cytarabine (ara-C) in combination with ATRA in newly diagnosed acute promyelocytic leukemia (APL), followed by consolidation and 3 years maintenance therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
1
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 44 publications
2
104
1
5
Order By: Relevance
“…The long-term data confirm and extend initial results on 51 patients published earlier. 19 The relapse rate of 11.4% after 10 years is less than half compared with the data of the literature for high risk APL treated without HD ara-C. 2,6,8,9 Figure 3 Relapse free survival. (a) Of all patients (n ¼ 131), who entered remission and (b) according to initial white blood cell count o or X10 Â 10 9 /l (P ¼ 0.83).…”
Section: Discussionmentioning
confidence: 89%
“…The long-term data confirm and extend initial results on 51 patients published earlier. 19 The relapse rate of 11.4% after 10 years is less than half compared with the data of the literature for high risk APL treated without HD ara-C. 2,6,8,9 Figure 3 Relapse free survival. (a) Of all patients (n ¼ 131), who entered remission and (b) according to initial white blood cell count o or X10 Â 10 9 /l (P ¼ 0.83).…”
Section: Discussionmentioning
confidence: 89%
“…4 However, for high-risk (WBC count410 Â 10 9 /l) patients, large doses of Ara-C could act better. 2,4,56 Although ATRA plus chemotherapy gained great effects, there are still problems such as relapse, severe side effects of chemotherapy and so on. The 5-year relapse-free survival and overall survival (OS) from SIH were only around 34.0 and 52%.…”
mentioning
confidence: 99%
“…After combined double induction including high-dose ara-C and ATRA, there are no hematologic or clinical relapses until 3. years. 1 This is confirmed in the recent update of November 2000 with a longer follow-up (median 33 months) and a higher number of patients (n = 73). The rate of hematologic remission is 93%.…”
Section: Figurementioning
confidence: 63%
“…8 (5) Since the kinetics of molecular remission was identified as one of two prognostic factors in APL in the British trials, 6 the rapid achievement of molecular remission reported by us 1 again suggests an improvement of poor prognosis. (6) The low relapse rate in the AMLCG study 1 is not explained by a comparatively high cumulative anthracycline dosage. Given the dose equivalents used by the EORTC 9 as daunorubicin (DNR) 50 mg = mitoxantrone 12 mg = idarubicin 10 mg, the cumulative DNR equivalent of 485 mg/m 2 given during induction and consolidation in the AMLCG study remains within the dose ranges of the other trials, 4,6,7 even if maintenance treatment is included in the calculation.…”
Section: Figurementioning
confidence: 89%
See 1 more Smart Citation